Chemical reaction networks: Filipino contributions to their theory and its applications - Arceo, Carlene Perpetua P. (Animo Repository, 2019)
© 2019, Department of Science and Technology. All rights reserved. This paper reviews the theory of chemical reaction networks and the contributions of Filipino scientists to it. The modern theory of chemical reaction networks began in the early 1970´s with the work of American chemical engineers and chemists from Canada and Russia. The field was reshaped at the turn of the century with the emergence of systems biology and biologists, computer scientists, mathematicians, and researchers from other disciplines joining the collaborative efforts. Luis F. Razon, a chemical engineer, and Baltazar D. Aguda, a chemist, were the first Filipinos to contribute to the theory with their Ph.D. theses in 1985 and 1986, respectively. Over twenty-five years later in 2014, mathematicians from several Philippine universities revived the research – focusing on power law kinetic systems and biological applications – and contributing nine international publications since. The paper concludes with a description of their current research and some promising perspectives.